Developing eminence in STEMM: An interview study with talent development and STEMM experts. Issue 1 (1st February 2023) - Luo, Linlin; Stoeger, Heidrun
Abstract: In the present day, we need outstanding scientists, engineers, mathematicians, and medical science researchers more than ever to solve the world's most pressing issues, such as climate change, water contamination, and cyber security. Naturally, we ask the question: What does it take to develop eminence in science, technology, engineering, mathematics, and medical science (STEMM)? To answer this question, we interviewed two relevant groups of experts: 14 talent development researchers and 14 STEMM experts. The interview questions were developed based on the theoretical framework of the Actiotope Model of Giftedness and the related educational and learning capital approach that differentiates five types of exogenous resources (educational capital) and five types of endogenous resources (learning capital) that feed into talent development toward eminence. The results show that all types of capital were regarded as important by the experts for developing eminence in STEMM. However, there were also differences. We describe the educational and learning capital that talent development researchers and STEMM experts considered to be important for talent development in STEMM, as well as the similarities and differences between the two groups.